Actionable vascular and other incidental findings on CTA in patients undergoing acute stroke intervention. Issue 6 (December 2018) - Kanesa-Thasan, Riti; Cox, Mougnyan; Patel, Manisha; Curtis, Brian; Hurst, Robert W; Kung, David; Flanders, Adam E
Providing a fast and accurate diagnosis of acute large-vessel occlusion on computed tomography angiograms (CTAs) is essential for timely intervention and good stroke outcomes. However, the detection and appropriate management of incidental findings are also important parts of any clinical radiology practice and can greatly affect patient care. The intricate anatomy covered by CTAs of the head and neck coupled with the time pressures of acute stroke diagnosis creates an environment in which unrelated, important findings can potentially be missed. The purpose of our study was to document clinically actionable incidental findings on CTA in 225 patients undergoing acute stroke intervention. After institutional review board approval, a retrospective six-year review of CTAs of the head and neck in patients undergoing acute stroke intervention was performed for actionable incidental vascular and nonvascular findings. A total of 225 patients undergoing acute stroke intervention with documented intracranial large-vessel occlusion on CTAs were consecutively enrolled in the study. Incidental vascular findings were identified in 17 of 225 patients (7.5%, 95% confidence interval 5% to 12%). Previously unreported aneurysms ranging from 2 mm to 10 mm in size represented 18 of 19 vascular findings in these patients. Incidental nonvascular findings were identified in 32 patients (14%, 95% confidence interval 5% to 12%). These included malpositioned support lines and tubes; pneumothorax; interstitial lung disease; newly diagnosed metastatic disease; nasopharyngeal, parotid, and pituitary masses; and cervical spine compression fractures. CTAs of the head and neck in patients undergoing acute stroke intervention contain a relatively high frequency of vascular and nonvascular incidental findings requiring further follow-up, and therefore should be evaluated carefully and systematically.